Recent Spatiotemporal Patterns of US Lung Cancer by Histologic Type - Lewis, Denise Riedel; Pickle, Linda W.; Zhu, Li (Frontiers in Public Health, 2017)
Abstract Background: After a period of increasing rates, lung cancer incidence is declining in the United States for men and women. We investigated lung cancer rate patterns by gender, geographic location and histologic subtype, and for total lung cancer (TLC), for the entire study period, for 2000 to 2011 from 17 Surveillance, Epidemiology and End Results (SEER) areas. Methods: For each gender-histologic type combination, time trend plots and maps of age-adjusted rates are presented. Time trend significance was tested by Joinpoint regression analysis. Spatial random effects models were applied to examine effects of sociodemographic factors, health insurance coverage, smoking, physician density at the county level. Linked micromap plots illustrate patterns for important model predictors. Results: Declining incidence trends occurred for TLC (p<0.05, entire period). Squamous cell carcinoma trends increased for females only (p<0.05). Small cell carcinoma trends declined overall, p<0.05, but recently increased faster for females than males. Adenocarcinoma rates initially declined, but were significantly increasing by 2004, p<0.05. Counties with higher current smoking and family poverty were strongly associated with higher risk for all gender-histologic types (p<0.0001 for both variables). County socio-economic status was associated with higher risk for all lung cancer subtypes for females, p<0.02. Counties with more diagnostic radiologists were associated with higher TLC rates (p<0.03); counties with greater primary care physician access were associated with lower TLC rates (p<0.03). TLC incidence rates were higher in eastern and southern states than western areas. Male rates were higher than female rates along the West Coast. Males and females had similar small cell rate patterns, with higher rates in the Midwest and southeast. Squamous cell carcinoma and adenocarcinoma rate patterns were similar to TLC patterns, except for relatively higher female adenocarcinoma rates in the northeast and northwest. Conclusions: Geographic patterns and declining time trends for incident lung cancer are consistent with previous mortality patterns. Male-female time trend and geographic pattern differences occur by histologic type. Time trends remain significant, even after adjustment for significant covariates. Knowledge of the variation of lung cancer incidence by region and histologic type is useful for surveillance and for implementing lung cancer control efforts.